0662 Comparative efficacy of digital CBT-I versus stepped-care CBT-I to prevent depression. (25th May 2022) - Cheng, Philip; Kalmbach, David; Sultan, Zain; Fellman-Couture, Cynthia; Drake, Christopher
Abstract: Introduction: Insomnia is a robust risk factor for depression. Treating insomnia with digital CBT-I (dCBT-I) has been shown to prevent future episodes of depression; however, remission rate of insomnia following dCBT-I is lower compared to face-to-face CBT-I (fCBT-I), which may reduce the effect on depression prevention. A stepped-care model can optimize care by starting with a least resource intensive intervention (step 1: dCBT-I) and stepping-up non-remitters to specialized treatment (step 2: face-to-face CBT-I). This study examined the efficacy of a stepped-care approach to prevent depression. Methods: 341 individuals with DSM-5 insomnia and no depression were randomized into two conditions at step 1: dCBT-I (n=161), or an online sleep education control (n=188). Participants in the dCBT-I condition who did not show remission for insomnia (ISI>9) were further randomized to either face-to-face CBT-I (n=40) or sleep education (n=47). Rates of clinically significant depression was assessed post-step 2. Results: Insomnia remission rates were higher in the dCBT-I group (46%) compared to the control group (22%); however, 54% remained symptomatic after dCBT-I and were rerandomized to step 2 treatments (fCBT-I or sleep education control). Insomnia remission rates following fCBT-I was 70% compared to 23% in the step 2 control.Rate of depression in those who received step 2 control (following non-remission to dCBT-I in step 1; 15%) was not significantly different from the step 1 control group (20%). In contrast, those who received step 2 fCBT-I reported significantly lower rates of depression (5%, OR=.22, p < .05) compared to the step 1 control. Those who remitted to dCBT-I in step 1 also reported comparably low rates of depression (8%, OR=.36, p < .05) Conclusion: Preliminary evidence from this study provide supported that a stepped-care approach may produce greater protection against incident depression than dCBT-I alone. Support (If Any): R01MH122636